Changing expertise and the state - Risto Rinne; Xingguo Zhou; Jaakko Kauko; Romuald Normand; Anna Medvedeva; Íris Santos (Routledge, 2022)
Although the state is still a relevant and powerful concept in legitimising actors and directing policy, legitimation through data ownership and experts’ instrumental knowledge has become a means of finding more room for action. Several studies have affirmed the role of knowledge in the shaping of education policy and implementation of education reforms on both national and global levels (Normand 2017; Lawn & Normand 2014). Expertise plays a crucial role in the production and interpreting of knowledge. It is “a specific activity of knowledge production participating in the process of negotiation and orientation of public policy” (Normand 2017: p. 74; see also Ozga 2011). This knowledge is mainly technical and prescriptive/normative and derives from the “professionals working in administrations of the states, international organisations, universities and the HE institutions, agencies, think tanks or interest groups” (Normand 2017: p. 74; see also Weible 2008). Policy arenas like consensus conferences are also central to the academic production of knowledge with various structures and conditions of reception (see Weiss 1979).
Politics of Quality in Education: A Comparative Study of Brazil, China, and Russia